Brave new 'RNA' world—advances in RNA tools and their application for understanding and engineering biological systems. Issue 14 (April 2019) - Ameruoso, Andrea; Gambill, Lauren; Liu, Baiyang; Villegas Kcam, Maria Claudia; Chappell, James
Abstract: Our ability to program how cells express their genetic material is central to our ability to understand and engineer them. While a range of biomolecules can be used to control gene expression, RNA is increasingly being turned to for this purpose. Here, we review recent progress in creating and applying RNA technologies for programming gene expression. First, we explore how new design approaches and regulatory systems are creating an increasingly versatile and robust RNA regulatory toolbox. Next, we describe how RNA is being applied to advance applications in engineering and fundamental studies of biological systems. Finally, we discuss the future perspectives of RNA tools and consider how they might be expanded in the coming years.